A competition analysis of the single and double disciplines in world-class badminton - Gawin, W.; Beyer, C.; Seidler, M. (International Journal of Performance Analysis in Sport, 2015)
Competition analyses in badminton commonly focus on the singles disciplines while relatively few studies deal with the demands of the doubles disciplines. Knowledge about the characteristics of the doubles disciplines, however, is essential for coaches in elite badminton in order to set up specific endurance training. For this purpose, the time structure of 50 matches of the world's top ten players in the singles and doubles was investigated. The lowest work to rest ratios were observed in the doubles disciplines (approximately 20 %) except for the ladies' doubles with 30.1 %. Furthermore, the ladies' doubles consisted of the longest rallies on average (10.1 s) whilst the rest times did not differ significantly between the disciplines. The men's and mixed doubles were characterized by the shortest mean rally times of 5.6-6.7 seconds and the highest number of shots per second. These empirical data confirmed the assumed differences between the ladies' doubles and the other doubles disciplines. When setting up specific training drills the higher frequencies in the doubles disciplines should be taken into consideration. The most common work intervals of 6-10 seconds should be applied and drills with the longest possible work intervals should be incorporated into the specific endurance training.